Accounting for Thermal Resistance of Cooling Water Fouling in Plate Heat Exchangers - Arsenyeva, O. P.; Tovazhnyanskyy, Leonid Leonidovich; Kapustenko, P. O.; Demirskyy, O. V. (The Italian Association of Chemical Engineering, 2012)
The Plate Heat Exchanger (PHE) is one of the most efficient types of modern heat exchangers. Heat transfer enhancement is one of the main features of PHEs, and lower fouling tendencies render them even more advantages for the use in different applications. The effects on fouling accumulation rate of process parameters in PHE channels of intricate geometry are studied in this article. The asymptotic behavior of the water fouling on heat transfer surfaces is examined. The fouling accumulation rate is described as a difference between the fouling deposition term and the fouling removal term. On comparison with data for fouling on different heat transfer surfaces available in literature it is shown that asymptotic fouling thermal resistance inversely proportional to wall shear stress. The proportionality coefficient in this relation is determined for a number of considered cases. To calculate the wall shear stress the equation for PHE channel main corrugated field is used, which accounts for corrugations geometrical parameters. It is shown that for given fouling properties of water this coefficient is constant and can be determined by monitoring fouling behavior of any item of heat exchangers working on specific enterprise. After that all other heat exchangers of that enterprise can be calculated using that data and developed Equation for accounting of fouling in their design.